2021
DOI: 10.1186/s12944-021-01547-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression level of ANGPTL8 in white adipose tissue under acute and chronic cold treatment

Abstract: Background Angiopoietin-like proteins (ANGPTL), primarily 3, 4, and 8, play a major role in maintaining energy homeostasis by regulating triglyceride metabolism. This study evaluated the level of ANGPTL3, 4, and 8 in the liver, brown adipose tissue (BAT), and subcutaneous white adipose tissue (SAT) of mice maintained under acute and chronic cold conditions. Methods C57BL/6J mice were exposed to cold temperature (4 °C) for 10 days with food provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The increase in metabolism as ambient temperature fell below the LCT was correlated with increased levels of T3, expansion of the BAT mass, increases in BAT mitochondrial protein, BAT COX activity and direct measures of non-shivering thermogenesis. These observations all support extensive previous work showing thermogenesis after about 10 days of cold exposure is provided predominantly by elevated heat production in BAT [ 26 , [76] , [77] , [78] ]. Our work shows that these responses are closely calibrated to the exact levels of cold, and the thermoregulatory requirements to sustain body temperature.…”
Section: Discussionsupporting
confidence: 91%
“…The increase in metabolism as ambient temperature fell below the LCT was correlated with increased levels of T3, expansion of the BAT mass, increases in BAT mitochondrial protein, BAT COX activity and direct measures of non-shivering thermogenesis. These observations all support extensive previous work showing thermogenesis after about 10 days of cold exposure is provided predominantly by elevated heat production in BAT [ 26 , [76] , [77] , [78] ]. Our work shows that these responses are closely calibrated to the exact levels of cold, and the thermoregulatory requirements to sustain body temperature.…”
Section: Discussionsupporting
confidence: 91%
“…angptl8 is regulated by nutritional and hormonal factors, and feeding induces an increase in its levels (192). It has been reported that ANGPTL8 not only induces the expression of brown adipocyte markers (193) but also promotes subcutaneous white adipose tissue (SAT) browning under acute and chronic hypothermic conditions (194). Fibroblast growth factor 21 (FGF21) is known to be a hepatokine induced by fasting and is being pursued as a therapeutic target for diabetes and obesity due to its rapid and effective action in improving insulin sensitivity (195).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%